2005
DOI: 10.1086/430523
|View full text |Cite
|
Sign up to set email alerts
|

Stellar Lyα Emission Lines in the Hubble Space Telescope Archive: Intrinsic Line Fluxes and Absorption from the Heliosphere and Astrospheres

Abstract: We search the Hubble Space Telescope (HST) archive for previously unanalyzed observations of stellar H I Lyα emission lines, our primary purpose being to look for new detections of Lyα absorption from the outer heliosphere, and to also search for analogous absorption from the astrospheres surrounding the observed stars. The astrospheric absorption is of particular interest because it can be used to study solar-like stellar winds that are otherwise undetectable. We find and analyze 33 HST Lyα spectra in the arc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
384
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 260 publications
(412 citation statements)
references
References 103 publications
(94 reference statements)
26
384
2
Order By: Relevance
“…4). The resulting profile shows a double peak emission, which is usually seen in the Lyman-α line of cool stars, and can be interpreted as self-absorption in the chromosphere of the star (Wood et al 2005).…”
Section: Resulting Spectramentioning
confidence: 92%
See 1 more Smart Citation
“…4). The resulting profile shows a double peak emission, which is usually seen in the Lyman-α line of cool stars, and can be interpreted as self-absorption in the chromosphere of the star (Wood et al 2005).…”
Section: Resulting Spectramentioning
confidence: 92%
“…As a result, the spectrally resolved line, at the resolution of the G140M spectrograph, is composed of two peaks separated by this deep absorption. In order to estimate the Lyman-α line flux and profile, we fitted the line profile as observed in September 2011, following the method of Wood et al (2005) and Ehrenreich et al (2011). The best result was obtained by modeling the stellar emission line using two Voigt profiles with the same width and damping constant.…”
Section: Resulting Spectramentioning
confidence: 99%
“…Wood et al (2005) investigated ISM and astrospheric absorption in Lyα profiles of more than 60 late-type stars. These authors showed that the ISM absorption in Lyα is much stronger than the astrospheric absorption.…”
Section: Correction For Ism Absorptionmentioning
confidence: 99%
“…2.1.2). This heliospheric hydrogen produces a Lyα absorption signature that has been detected in some HST spectra (Linsky and Wood 1996;Wood et al 2005). The heliospheric contribution to the hydrogen wall can be completely obscured by the interstellar absorption if the ISMa column density is too high and the ISMa absorption therefore too broad.…”
Section: Anomalous Cosmic Rays and Heliospheric Asymmetriesmentioning
confidence: 84%
“…Most detections of heliospheric absorption sample this population, and originate near the upwind direction of the CHISM flow, because this is where the heating, compression, and deceleration of the ISMa neutrals is strongest. Deceleration of the H • flow in the radial direction is required to separate the heliospheric absorption from that of the ISMa (Wood et al 2005). Several studies have demonstrated that hydrodynamic models of the heliosphere can reproduce the observed kinematic characteristics of the hydrogen wall absorption, depending on exactly what is assumed about the properties of the CHISM (Gayley et al 1997;Wood et al 2000aWood et al , 2007.…”
Section: Anomalous Cosmic Rays and Heliospheric Asymmetriesmentioning
confidence: 99%